Photoreductive generation of amorphous bismuth nanoparticles using polysaccharides – Bismuth–cellulose nanocomposites. (13th February 2015) - Breitwieser, Doris; Kriechbaum, Margit; Ehmann, Heike M.A.; Monkowius, Uwe; Coseri, Sergiu; Sacarescu, Liviu; Spirk, Stefan
Highlights: Bismuth nanoparticles are synthesized by photoreduction. The nanoparticles are stabilized by a trimethylsilyl cellulose matrix. Particle sizes are around 20 nm. Silyl groups can be cleaved off to yield cellulose films. Abstract: A simple and highly reproducible synthesis of amorphous bismuth nanoparticles incorporated into a polysaccharide matrix using a photoreduction process is presented. As precursor for the generation of the Bi nanoparticles, organosoluble triphenylbismuth is used. The precursor is dissolved in toluene and mixed with a hydrophobic organosoluble polysaccharide, namely trimethylsilyl cellulose (TMSC) with high DSSi . The solution is subjected to UV exposure, which induces the homolytic cleavage of the bismuth–carbon bond in BiPh3 resulting in the formation of Bi 0 and phenyl radicals. The aggregation of the Bi atoms can be controlled in the TMSC matrix and yields nanoparticles of around 20 nm size as proven by TEM. The phenyl radicals undergo recombination to form small organic molecules like benzene and biphenyl, which can be removed from the nanocomposite after lyophilization and exposure to high vacuum. Finally, the TMSC matrix is converted to cellulose after exposure to HCl vapors, which remove the trimethylsilyl groups from the TMSC derivative. Although TMSC is converted to cellulose, the formed TMS-OH is not leaving the nanocomposite but reacts instead with surface oxide layer of the Bi nanoparticles to form silylated Bi nanoparticles as proven by TEM/EDX.